Kajian Deskriptif tentang Kondisi Faktor Intrinsik dan Ekstrinsik serta Kepuasan Kerja Manajer Menengah-Bawah - Noermijati Noermijati (Jurnal Aplikasi Manajemen, 2010)
This research is discussing about the condition of intrinsic and ekstrinsic factors, and job satisfaction midle-lower managers in small cigarettes company in Malang. This researh is using descriptive qualitatve analysis, with 47 companies agreed to e researched Respondents in this research are 157 midlelower managers in those 47 companies. Then, using frequency and mean as data analysis method, which the result then being described. Research variable include intrinsic factor, extrinsic factor and job satisfaction.  The rsult shows that the existence of intrinsic factor in the company is sufficient. From the discrlptive analysts on intrinsic variable, it can be concluded that the operational managers realize the importance of job achievement they have to reach to ensure their compani’s survival. The mean of extrinsic variable shows that the existance of this variable is sufficient to to keep the work condition in the company. From the descriptive analysis toward this variable, can he concluded that the perational managers realze the importance of relationship with co-workers, and this encourages respondent enjoy working in the company, although the facility is not the same with tyeir expectation. And the level of midle-lower manager job satisfaction is still in the medium to low level.